Determinants of Financial Inclusion in Namobuddha Municipality, Nepal (The International Research Journal of Management Science, 2021)
Financial inclusion is a priority agenda in countries like Nepal. The study seeks to determine the access to financial services, financial innovation and quality of financial services to the financial inclusion.The study is based on questionnaire surveydata with363 household respondents using a convenient sampling technique, and carried out in Namobuddha Municipality of Nepal. The moderating effect of financial literacy and control variable of demographic items have been analysed using generalised regression model. The results show that financial innovation and quality of financial services are the significant determinants of financial inclusion; financial literacy is found significant and it plays a moderating role between the variables under study. The findings revealed that the tendency of higher level of financial inclusion was influenced by gender, education level and monthly income.